The reorganization of global value chains: What's in it for Latin America and the Caribbean? : technical appendix - Mauricio Mesquita Moreira; Juan S. Blyde; Christian Volpe Martincus; Marcelo Dolabella; Ignacio Marra de Arti\~nano (Inter-American Development Bank (IDB), 2022)
Online Technical Appendix to "The Reorganization of Global Value Chains: What's in it for Latin America and the Caribbean?" It describes in more detail the data sources, the empirical strategy; and presents a series of robustness checks.
Keywords: 330; Value Chains; Trade; Latin America; Nearshoring